An exploration of Business Studies Teachers' integration of Information and Communication Technologies to equip Grade 12 learners with critical business skills - Gcabanshe, Nduduzo Brian (University of the Witwatersrand, Johannesburg, 2024)
Business studies is a subject that in South African schools to equip learners with skills that would enable them to operate effectively in contemporary business environment, either as employers or employees. However,there is a general concern that learners who are produced by these schools do not possess skills that are relevant to current business environments. This is partly due to the impact of technological developments that continue to cause a shift in skills needed by businesses. Therefore, there is a need for an exploration on how best business studies teachers integrate ICTs in their classrooms to equip learners with skills that are required by the contemporary business environment. This study explored ICT integration by business studies teachers to equip Grade 12 learners with critical business skills that are required by the contemporary business environment. Social Constructivism Theory and Functional Context Theory were adopted as the theoretical lenses of this study. Social Constructivists emphasize the need for interaction, collaboration, active learning, and autonomous learning in the learning context for meaningful learning to occur. Functional Context Theory, on the other hand, advocates for a learning environment that reflects the world for which learners are being prepared for. The proponents of this theory advise teachers to integrate resources that learners would use upon joining the real world of work. This is a qualitative study underpinned by the interpretive research paradigm. A multi case study research design was deemed suitable for this particular study. Face-to- face individual interviews and classroom observations were adopted to collect data. Six Business Studies teachers who use ICTs to teach were selected from six secondary schools located in Kwa-Zulu Natal province of South Africa were iv purposively sampled. Data that was collected were analyzed using hybrid thematic analysis. Findings of the study were that: i. teachers see value in ICT integration in their business studies pedagogical practices. teachers see ICTs as tools that assist in exposing learners to authentic learning activities that help them to acquire critical business skills needed by the contemporary business environment. business studies teachers adopted various learner-centred teaching methods to create learning environments that promote the acquisition of critical business skills. iv. most teachers integrated different ICTs to nurture learners’ critical business skills. teachers mainly relied on their personal teaching experiences and their generic technological skills. Based on the findings of this study, Technology Integration Model for Business Studies teachers was developed. The developed framework can play a role in helping business studies teachers integrate ICTs in a systematic way that would lead to learners’ acquisition of critical business skills. Based on the key findings highlighted above, the study recommends that the Department of Basic Education (DBE) should develop coherent professional development programmes to expose all business studies teachers to novel pedagogies, learning activities and ICTs that can be used to nurture learners’ critical v business skills. This will help to reduce teachers’ over reliance on their teaching experiences and what they think is suitable for learners to acquire critical business skills, which sometimes can be inconsistent with the objectives of the business studies curriculum.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Business studies; critical business skills; teachers; teaching methods; ICT integration; SDG-4: Quality education